In vivo action of RNA G-quadruplex in phloem development - Cho, Hyunwoo; Cho, Hyun Seob; Hwang, Ildoo (BMB reports, 2018)
Hyunwoo Cho, Hyun Seob Cho, and Ildoo Hwang. BMB Reports 2018;51:547-8. https://doi.org/10.5483/BMBRep.2018.51.11.253